1984
DOI: 10.1007/bf00023415
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of physical stress responses in soybean seedlings using cloned heat shock cDNAs

Abstract: Soybean seedlings were subjected to a wide range of physical (abiotic) or environmental stresses. Cloned cDNAs to heat shock (hs)-induced mRNAs were used to assess whether these diverse stresses induced the accumulation of poly(A)RNAs in common with those induced by hs. Northern blot hybridization analyses indicated that a wide range of stress agents lead to the accumulation of detectable levels of several of the hs-induced poly(A)RNAs; the relative concentration of those RNAs 'induced' by the wide range of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
104
2

Year Published

1987
1987
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(115 citation statements)
references
References 60 publications
(74 reference statements)
9
104
2
Order By: Relevance
“…The 14.1-kD alternative protein, still containing the GSHbinding site encoded within the first exon of Bz2, could bind the GSH moiety of a PC-cadmium complex, perhaps assisting in the sequestration of PC-cadmium complexes to the vacuole through the heavy metal transporter (HMT1) shown to be responsible for PC-cadmium transport into vacuoles (Ortiz et al, 1995). Previous investigators have speculated that truncated proteins could be produced from the unprocessed versions of the hsp70 and GmGST26-A messages (Czarnecka et al, 1984(Czarnecka et al, , 1988Winter et al, 1988). Czarnecka et al (1984) showed that both a 26-kD, full-length GmGST26-A protein and a 13-to 15-kD truncated protein could be in vitro translated during cadmium stress.…”
Section: Sc Ussl Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The 14.1-kD alternative protein, still containing the GSHbinding site encoded within the first exon of Bz2, could bind the GSH moiety of a PC-cadmium complex, perhaps assisting in the sequestration of PC-cadmium complexes to the vacuole through the heavy metal transporter (HMT1) shown to be responsible for PC-cadmium transport into vacuoles (Ortiz et al, 1995). Previous investigators have speculated that truncated proteins could be produced from the unprocessed versions of the hsp70 and GmGST26-A messages (Czarnecka et al, 1984(Czarnecka et al, , 1988Winter et al, 1988). Czarnecka et al (1984) showed that both a 26-kD, full-length GmGST26-A protein and a 13-to 15-kD truncated protein could be in vitro translated during cadmium stress.…”
Section: Sc Ussl Onmentioning
confidence: 99%
“…Previous investigators have speculated that truncated proteins could be produced from the unprocessed versions of the hsp70 and GmGST26-A messages (Czarnecka et al, 1984(Czarnecka et al, , 1988Winter et al, 1988). Czarnecka et al (1984) showed that both a 26-kD, full-length GmGST26-A protein and a 13-to 15-kD truncated protein could be in vitro translated during cadmium stress. A truncated BZ2 protein produced during cadmium stress from the unspliced Bz2 mRNA is currently being investigated in our laboratory (J.C. Urioste, unpublished results).…”
Section: Sc Ussl Onmentioning
confidence: 99%
“…Isolation of RNA from SB-P cells and Northern blot analyses were performed as described (15). 32P-labeled DNA probes were prepared by random-primer labeling of the isolated cDNA inserts of soybean cab and hsp75 and maize 17S rRNA for detection of the soybean 18S rRNA (16)(17)(18) (Fig. 1A).…”
mentioning
confidence: 99%
“…The HSR of higher plants is similar to that of other organisms. The HSPs have been characterized in great detail in soybean (10,16,17,20), maize (4, 9), tobacco (11,15), and tomato (25). …”
mentioning
confidence: 99%
“…The HSR of higher plants is similar to that of other organisms. The HSPs have been characterized in great detail in soybean (10,16,17,20), maize (4,9), tobacco (11,15), and tomato (25). The soybean HSPs are also induced by other forms of stress such as arsenite; however, the proteins are not localized in the cell as they are under heat shock conditions (10).…”
mentioning
confidence: 99%